Salivary miR-93 and miR-200a as post-radiotherapy biomarkers in head and neck squamous cell carcinoma - Greither, Thomas; Vorwerk, Freya; Kappler, Matthias; Bache, Matthias; Taubert, Helge; Kuhnt, Thomas; Hey, Jeremias; Eckert, Alexander W. (Oncology Reports, 2017)
Head and neck squamous cell carcinoma is the 6th most malignant tumor entity worldwide and has exhibited a 5-year mortality of approximately 50% for the last fifty years. For the therapy monitoring and successful management of this tumor entity new and easily accessible biomarkers are greatly needed. The aim of the study was to determine whether and to what extent microRNAs, a class of small regulatory RNAs, are detectable in saliva post-radiation therapy. The expression and feasibility as therapy monitoring marker of the microRNAs were analyzed by RT-qPCR in 83 saliva samples from 33 patients collected at several time points pre-, during and post-radiotherapy treatment. Ten head and neck squamous cell carcinoma- or radiation-associated microRNAs (miR-93, miR-125a, miR-142-3p, miR-200a, miR-203, miR-213, let-7a, let-7b, let-7g and let-7i) were analyzed. All were detectable to a different extent in the saliva of the patients. miR-93 and miR-200a were significantly higher expressed 12 months post radiotherapy than at baseline (p=0.047 and p=0.036). These results point towards miR-93 and miR-200a as biomarkers for the treatment monitoring post-radiation of head and neck squamous cell carcinoma.
EVALuna2:35921